CMOS analog IC design for 5G and beyond - Singh, Sangeeta; Arya, Rajeev; Singh, M. P.; Iyer, Brijesh (Springer, 2021)
This book is focused on addressing the designs of FinFET-based analog ICs for 5G and E-band communication networks. In addition, it also incorporates some of the contemporary developments over different fields. It highlights the latest advances, problems and challenges and presents the latest research results in the field of mm-wave integrated circuits designing based on scientific literature and its practical realization. The traditional approaches are excluded in this book. The authors cover various design guidelines to be taken care for while designing these circuits and detrimental scaling effects on the same. Moreover, Gallium Nitrides (GaN) are also reported to show huge potentials for the power amplifier designing required in 5G communication network. Subsequently, to enhance the readability of this book, the authors also include real-time problems in RFIC designing, case studies from experimental results, and clearly demarking design guidelines for the 5G communication ICs designing. This book incorporates the most recent FinFET architecture for the analog IC designing and the scaling effects along with the GaN technology as well.